The Francis Effect on the Munus Docendi and Gubernandi of the Church - Bretzke, James T. (Horizons, 2015)
Many observers detect a noticeable change in tone and practice between the pontificates of John Paul II and Benedict XVI on the one hand, and that of Francis on the other, a shift from what some have called a more rigorously doctrinal and juridical approach to a more inclusive and pastoral one. This change has been dubbed "the Francis Effect," and numerous commentators have attempted to discern its fundamental characteristics and its impact on the wider church. This roundtable, based on a "reading of the Roman tea leaves" first proposed by James T. Bretzke, SJ, at the 2015 College Theology Society Annual Convention and revised for this issue, offers an interpretation that focuses on the service (munus) of teaching and governing exercised by the pope and its practical impact on the church. In their responses to Bretzke, Julie Hanlon Rubio and Reid Locklin explore this impact further and point out both the strengths and the limits of the Francis Effect.1